2021
DOI: 10.15809/irriga.2021v1n4p704-713
|View full text |Cite
|
Sign up to set email alerts
|

Água Salina E Adubação Fosfatada Na Cultura Do Amendoim

Abstract: ÁGUA SALINA E ADUBAÇÃO FOSFATADA NA CULTURA DO AMENDOIM     JOSÉ MARCELO DA SILVA GUILHERME1; GEOCLEBER GOMES DE SOUSA2; SAMUEL DE OLIVEIRA SANTOS3; KRISHNA RIBEIRO GOMES4; THALES VINICIUS DE ARAÚJO VIANA5   1 Mestrando pelo programa de pós graduação em engenharia agrícola da Universidade Federal do Ceará, Campus do Pici (Av. Mister Hull, 2977, Pici, 60.021-970, Fortaleza, Ceará, Brasil). E-mail: jose.marcelo98@gmail.com 2Professor Doutor, Instituto de Desenvolvimento Rural, Universidade da Integração Internac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Reductions in the substrate's water potential due to the accumulation of salts can induce greater energy expenditure to maintain metabolic activities, which results in damage to plant development, such as smaller fruit diameter (Silva et al, 2019). Similar to the results obtained in this study, Guilherme et al (2021) observed a reduction in pod diameter values in peanut plants subjected to irrigation with brackish water.…”
Section: Resultssupporting
confidence: 91%
“…Reductions in the substrate's water potential due to the accumulation of salts can induce greater energy expenditure to maintain metabolic activities, which results in damage to plant development, such as smaller fruit diameter (Silva et al, 2019). Similar to the results obtained in this study, Guilherme et al (2021) observed a reduction in pod diameter values in peanut plants subjected to irrigation with brackish water.…”
Section: Resultssupporting
confidence: 91%
“…(Khan et al, 2023). Similar results were observed by Guilherme et al (2021) when analyzing the use of saline water and phosphate fertilization in peanut crop and found that higher doses of P, increased the length of pods of peanut plants when subjected to irrigation with saline water.…”
Section: Resultssupporting
confidence: 80%
“…N when supplied in the proper concentration can act in metabolic pathways, such as the assimilation of amino acids that will be synthesized in the leaves or roots, subsequently distributed and allocated to N needs of crops (Yang et al, 2020;Taiz et al, 2017). As well as N supplied in the proper concentration, P has as one of its main functions the action of energy transport of the cell in the form of adenosine triphosphate (ATP) (Guilherme et al, 2021). K, on the other hand, acts in the processes of transpiration and photosynthesis, distribution of carbohydrates, photoassimilates and phytohormones (Ferreira et al, 2020;Silva et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Peanut (Arachis hypogaea L.), which belongs to the Fabaceae family, is the fourth most sown oilseed crop in the world and is cultivated on a large scale in the Americas, Africa, and Asia. It is considered one of the foremost industrial and food crops worldwide, and is beneficial for human nutrition, both in raw and processed form, or used for oil production (Arruda et al, 2015;Goes et al, 2021;Guilherme et al, 2021).…”
Section: Introductionmentioning
confidence: 99%